The Internal Morality of Contracting: Advancing the Contractualist Endeavor in Business Ethics - van Oosterhout, J. (Hans); Heugens, Pursey P. M. A. R.; Kaptein, Muel (Academy of Management Review, 2006)
Integrative social contracts theory is arguably the most promising theory of business ethics to date, but often criticized for its inability to produce substantive, action-guiding norms. Rather than importing moral substance from outside the contractualist framework, or abandoning contractualist business ethics (CBE) altogether, we seek to advance CBE by exploring the internal morality of contracting. We demonstrate that substantive norms for guiding and constraining business conduct can be produced without relying on premises from outside the contractualist framework.